Dampak Kebiasaan Merokok terhadap Risiko Anestesi dan Pembedahan - Sinta Maharani Fawwaz; Dimas Kusnugroho Bonardo Pardede (Cermin Dunia Kedokteran, 2023)
Smoking has negative impact not only to general health but also to surgical outcome by increasing risks of perioperative complications. Perioperative complications due to smoking are cardiopulmonary and neurologic adverse events, altered metabolism of anesthetic drugs, difficult to control postoperative pain, delayed wound healing, and surgical site infection. Stopping smoking before surgery has been shown to decrease the risk of perioperative complications. Perioperative period may provide a teachable momentum for smoking cessation programme and eventually quit smoking.